2013
DOI: 10.1155/2013/629235
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Modifies the Regulation Exerted by Testosterone on 5α-Reductase Isozymes in Ventral Prostate of Adult Rats

Abstract: The development, growth, and function of the prostate gland depend on androgen stimulation. The primary androgen in prostate is 5α-dihydrotestosterone (DHT) which is synthesized from circulating testosterone (T) through the action of 5α-reductase (5α-R). Although 5α-R occurs as five isozymes, only 5α-R1 and 5α-R2 are physiologically involved in steroidogenesis. The endocrine disruptor bisphenol A (BPA) alters sexual organs, including the prostate. Our previous findings indicated that BPA decreased the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
1
7
0
1
Order By: Relevance
“…One example of such a substance is the anti-androgenic drug and 5a-reductase inhibitor finasteride (Clark et al 1990, Bowman et al 2003, Christiansen et al 2009). Interestingly, a new study that examines the effects of short-term exposure to BPA on mRNA levels of 5a-reductase isozymes in prostate of adult castrated rats show that BPA significantly decreased the mRNA levels of both 5a-reductase isozymes (Sánchez et al 2013). This indicates that BPA is a 5a-reductase inhibitor and could be one explanation for the shallow dose-response similarly as for finasteride.…”
Section: Discussionmentioning
confidence: 99%
“…One example of such a substance is the anti-androgenic drug and 5a-reductase inhibitor finasteride (Clark et al 1990, Bowman et al 2003, Christiansen et al 2009). Interestingly, a new study that examines the effects of short-term exposure to BPA on mRNA levels of 5a-reductase isozymes in prostate of adult castrated rats show that BPA significantly decreased the mRNA levels of both 5a-reductase isozymes (Sánchez et al 2013). This indicates that BPA is a 5a-reductase inhibitor and could be one explanation for the shallow dose-response similarly as for finasteride.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may reflect temporal or compensatory effects as a result of differential exposure times, or dose-dependent mechanisms (Vandenberg et al, 2012). Another possibility is that BPA, due to its anti-androgenic activity through androgen receptor (AR) antagonism (Lee et al, 2003;Sánchez et al, 2013), might differentially regulate 5α-R1 and Fig. 2.…”
Section: Effects On 5α-r Isozymesmentioning
confidence: 99%
“…Treatment with increasing concentrations of BPA (1 to 1,000 nM) did not significantly lower basal or hCG-stimulated T secretion by primary culture of LCs of young adult male rats ( 42 ). However, although Sánchez et al reported that low-dose BPA did not decrease T levels in Wistar rats, dihydrotestosterone levels decreased ( 43 ). Gamez et al reported that exposure to low-dose BPA led to an increase in serum LH and FSH levels in young Wistar rats ( 44 ).…”
Section: Bisphenols and Testicular Steroidogenesismentioning
confidence: 98%